The clash of "E" and "S" of ESG: Just transition on the path to net zero and the implications for sustainable corporate governance and finance - Alperen A. Gözlügöl (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
Climate change is one of the highest-ranking issues on the political and social agenda. Vulnerabilities of the world ecosystem laid bare by the COVID-19 pandemic and the potential damage for the human and business life made the need for urgent action clear once again. Corporations are one of the main actors that will play a major role in the decarbonisation of the economy. They need to put forward a net zero strategy and targets, transitioning to net-zero by 2050. Yet, an important but rather overlooked stakeholder group in the sustainability debates can pose a significant stumbling block in this transition: employees. Although climate action has huge benefits by ameliorating adverse environmental events and is expected to have overall positive impact on employment, net zero transition in companies, especially in certain sectors and regions, will cause substantial adverse employment effects for the workforce. This has the potential to slow down or even derail the necessary climate action in companies. In this regard, just transition is a promising concept, which calls for a swift and decisive climate action in corporations while taking account of and mitigating adverse effects for their workforce. If well implemented, it can accelerate net zero transition in companies. This potential clash of environmental (E) and social (S) aspects of ESG agenda, materialised in the companies' net zero transition, and its potential remedy, just transition, have important implications for corporate governance and finance, especially for directors' duties & executive remuneration, sustainability disclosures, institutional investors' engagement and green finance.
urn:nbn:de:hebis:30:3-616398
Keywords: 330; ESG; climate change; corporate governance; employees; green finance; institutional investors; net zero transition; sustainability; workforce